2007
DOI: 10.1167/iovs.06-0248
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein, a Toxicant in Cigarette Smoke, Causes Oxidative Damage and Mitochondrial Dysfunction in RPE Cells: Protection by (R)-α-Lipoic Acid

Abstract: These results show that acrolein is a mitochondrial toxicant in RPE cells and that acrolein-induced oxidative mitochondrial dysfunction is reduced by lipoic acid. The similar sensitivity of the ARPE-19 and hfRPE cells suggests that both models are useful for studying RPE toxicity and protection. These experiments indicate that mitochondria-targeted antioxidants such as lipoic acid may be an effective strategy for reducing or preventing chronic oxidant-induced RPE degeneration in vivo from a variety of sources,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
136
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 39 publications
5
136
0
Order By: Relevance
“…To evaluate the effect of IHH on oxidative stress during I/R, we measured protein carbonyls and malondialdehyde (MDA), respective products of protein oxidation and lipid peroxidation (22,24), in LV tissue homogenated in protein lysis buffer without DTT. Protein carbonyls were measured using an immunoblot kit to detect the 2, 4-dinitrophenylhydrazine (DNPH) derivatization of protein carbonyls following the manufacturer's instruction (Cell Biolabs).…”
Section: Animalmentioning
confidence: 99%
“…To evaluate the effect of IHH on oxidative stress during I/R, we measured protein carbonyls and malondialdehyde (MDA), respective products of protein oxidation and lipid peroxidation (22,24), in LV tissue homogenated in protein lysis buffer without DTT. Protein carbonyls were measured using an immunoblot kit to detect the 2, 4-dinitrophenylhydrazine (DNPH) derivatization of protein carbonyls following the manufacturer's instruction (Cell Biolabs).…”
Section: Animalmentioning
confidence: 99%
“…Although the mechanism underlying the environmental factors mediated increased risk of AMD is not known, it is believed that they may increase macular damage and/or alter the immune function. Taken cigarette smoking as an example, the blood borne products of tobacco combustion damage RPE cells, alter Bruch's membrane and exacerbate sub-PRE deposition (Bertram et al 2009, Espinosa-Heidmann et al 2006, Jia et al 2007, Wang et al 2009 (Jia et al 2007). Cigarette smoking also affects the immune system (Arnson et al 2010, Klareskog et al 2007, including the ocular immune responses.…”
Section: Age-related Macular Degeneration -An Imbalance Between Maculmentioning
confidence: 99%
“…Acrolein is a highly reactive unsaturated aldehydic product of lipid peroxidation that could implicate various degenerative pathogenesis, oxidative DNA damage and mutagenesis and is widely used as a positive control of reactive oxygen species (ROS) experiments (Jia et al, 2007;LoPachin et al, 2009;Luo & Shi, 2005;Pan et al, 2009;Roy et al, 2009;Wang et al, 2009;Zitting & Heinonen, 1980). However, protection against acrolein toxicity in endothelial cells by using the aqueous extract of Scutellaria baicalensis Georgi (Labiatae) (SbG) has not been investigated, though SbG has been reported to have anti-asthmatic, anti-fungal, antioxidative, and antiinflammatory activities (Huang et al, 2006;Koda et al, 1972;Wong & Tsang, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Past studies of SbG showed the neuroprotective effects on ROS-induced cytotoxicity in neuronal HT-22 cells, neuroblastoma SH-SY5Y cells and PC12 cells (Choi et al, 2002;Gao et al, 2001;Shang et al, 2006;Wang et al, 2009). SbG contains numerous flavone derivatives and the active components were studied (Ding et al, 2009;Jia et al, 2007;Yu et al, 2007). It is worthwhile to investigate whether the SbG also had protective effects on endothelial cells, which is of significant clinical meaning in treating endothelial cell related diseases.…”
Section: Introductionmentioning
confidence: 99%